Measurements of neutral B decay branching fractions to K-S(0)pi(+)pi(-) final states - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
Branching fraction measurements using B-meson decays to Ks0π+π- are presented. These measurements were obtained by analyzing a data sample of 88.9 × 106 Υ(45) → BB̄ decays collected with the BABAR detector at the SLAC PEP-II asymmetric-energy B factory. Using a maximum likelihood fit, the following branching fraction results were obtained: B(B0π +π-) = (43.7 ± 3.8 ± 3.4) × 10 -6, B(B0 → K*+π-) (12.9 ± 2.4 ± 1.4) × 10-6, and B(B0 → D-(→Ks0π+π -)π+) = (42.7 ± 2.1 ± 2.2) × 10-6. The CP violating charge asymmetry AK*π for the decay B0 → K*+π- was measured to be AK*π = 0.23 ± 0.18-0.06+0.09. For all these measurements the first error is statistical and the second is systematic.